The Least Developed Countries Report 2015 - United Nations Conference on Trade; Development (United Nations, 2015)
This report documents the importance of the rural sector and agriculture in least developed countries (LDCs), through employment generation and economic activity. The discussion is placed in the perspective of the post-2015 development agenda, in which rural economic transformation will be vital for poverty eradication. It presents evidence on agricultural productivity dynamics in LDCs, discussing the importance of agricultural productivity for human development in rural areas, and analyzing the key elements driving agricultural productivity growth in these countries. It examines the synergies and complementarities between agricultural productivity growth and rural economic diversification. It discusses policies which need to be put in place.